Anaerobic Resistance of Clinical Isolates of Staphylococcus aureus to Aminoglycosides - Harrell, Lizzie J. (1978)
The anaerobic minimum inhibitory concentration of six aminoglycosides (amikacin, gentamicin, kanamycin, netilmicin, sisomicin, and tobramycin) averaged over 10-fold greater than the aerobic minimum inhibitory concentration for 50 clinical isolates of Staphylococcus aureus. Cultures from osteomyelitis and blood generally showed a somewhat greater increase in minimum inhibitory concentration due to anaerobiosis than did cultures from abscesses and wounds, and amikacin activity was most affected by anaerobiosis.